United Kingdom : 2005 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Kingdom. (IMF Staff Country Reports; Country Report ;, 2006)
The United Kingdom's 2005 Article IV Consultation reports that macroeconomic performance has been strong and steady, owing in part to confidence-enhancing policy frameworks and generally sound implementation. The financial system is generally healthy, although a substantial increase in the pricing of risk would pose risks. The banking system is well-capitalized and highly profitable. The health of the insurance sector has improved substantially. Credit risk transfer instruments are helping to diversify credit risk, but their rapid growth may also be creating new risks.